Soil CO₂ Emissions in Jakarta Urban Forests: The Role of Canopy Cover Versus Environmental Factors - Elvira, Ade Irma; Arif, Ibrahim; Nainggolan, Carla Mariana; Renita, Destia Puri Prela; Putri, Nadia Asmawari; Patria, Mufti Petala; Nurdin, Nurdin; Vasenev, Ivan Ivanovich (Jurnal Manajemen Hutan Tropika, 2026)
Increasing carbon dioxide (CO2) emissions encourages global warming and climate change. Soil can store CO2 emissions, which are absorbed by vegetation. Studies on the dynamics of soil CO2 gas emission fluxes with differences in the percentage of vegetation canopy cover in the urban forest ecosystem of the Jakarta Region have never been frequently carried out. This research aims to analyze and compare the dynamics of soil CO2 gas emission fluxes in the urban forest ecosystem of the Jakarta Region with different percentages of vegetation canopy cover and analyze the relationship between air temperature, soil moisture, soil temperature, and soil acidity (pH) with carbon gas emission fluxes soil dioxide. The research method used is the greenhouse gas capture method, which uses a chamber to measure environmental factors and data analysis using the Kruskal-Wallis test and Spearman correlation. The results showed no significant difference between the percentage of vegetation canopy cover in the urban forest ecosystem and the soil CO2 gas emissions flux. Environmental factors related to the flux of CO2 emissions from soil in the urban forest ecosystem of the Jakarta Region are soil moisture and soil pH. Further research is recommended to measure other environmental factors, such as nutrients and soil organic carbon, to obtain more comprehensive research results on the dynamics of soil CO2 gas emission fluxes.